A trait–environment relationship approach to participatory plant breeding for organic agriculture. Issue 3 (24th May 2022) - Rolhauser, Andrés G.; Windfeld, Emma; Hanson, Solveig; Wittman, Hannah; Thoreau, Chris; Lyon, Alexandra; Isaac, Marney E.
Summary: The extent of intraspecific variation in trait–environment relationships is an open question with limited empirical support in crops. In organic agriculture, with high environmental heterogeneity, this knowledge could guide breeding programs to optimize crop attributes. We propose a three‐dimensional framework involving crop performance, crop traits, and environmental axes to uncover the multidimensionality of trait–environment relationships within a crop. We modeled instantaneous photosynthesis ( A sat ) and water‐use efficiency (WUE) as functions of four phenotypic traits, three soil variables, five carrot ( Daucus carota ) varieties, and their interactions in a national participatory plant breeding program involving a suite of farms across Canada. We used these interactions to describe the resulting 12 trait–environment relationships across varieties. We found one significant trait–environment relationship for A sat (taproot tissue density–soil phosphorus), which was consistent across varieties. For WUE, we found that three relationships (petiole diameter–soil nitrogen, petiole diameter–soil phosphorus, and leaf area–soil phosphorus) varied significantly across varieties. As a result, WUE was maximized by different combinations of trait values and soil conditions depending on the variety. Our three‐dimensional framework supports the identification of functional traits behind the differential responses of crop varieties to environmental variation and thus guides breeding programs to optimize crop attributes from an eco‐evolutionary perspective.